The Effect of Mindfulness-Based Counseling on Anxiety Management in Lecturers - Fitri, Jenny Marsya; Fitriani, Wahidah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
Lecturers often face significant mental health challenges, with anxiety emerging as one of the most prevalent issues within academic settings. Factors such as excessive workloads, research obligations, and administrative responsibilities frequently contribute to elevated anxiety levels. Among various therapeutic interventions, mindfulness-based counseling has demonstrated efficacy in alleviating anxiety symptoms. This study investigates the impact of mindfulness-based counseling on anxiety management among university lecturers. Adopting a quantitative experimental design, the research involved 50 lecturers from multiple universities in West Sumatra. The findings reveal that mindfulness-based counseling leads to a statistically significant reduction in anxiety levels. These results underscore the potential of mindfulness-based interventions as an effective method for enhancing the psychological well-being of lecturers. The intervention yielded an average reduction of approximately 12 points in HAM-A scores, affirming its therapeutic value. The integration of mindfulness-based counseling in academic institutions may not only improve lecturers’ mental health but also enhance the overall quality of teaching they deliver.